Targeted mass spectrometry of ketamine and its metabolites cis-6-hydroxynorketamine and norketamine in human blood serum - Kurzweil, Lisa; Danyeli, Lena; Şen, Zümrüt Duygu; Fejtová, Anna; Walter, Martin; Gensberger-Reigl, Sabrina (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2020)
Ketamine (KET) was originally developed as an anesthetic agent but has also attracted attention for further clinical applications such as medical treatment of depression or pain. The use of KET induces dissociation and emergence delirium. Due to these effects, KET has a high potential for abuse. In order to investigate metabolization of KET or to confirm misuse of KET, highly sensitive analytical methods that cover KET and its metabolites are necessary. A new analytical approach for simultaneous analysis of KET and its metabolites cis-6-hydroxynorketamine (HNK) and norketamine (NK) was established. The compounds were extracted from human blood serum by ultrafiltration and solid phase extraction with subsequent vacuum evaporation. The compounds were analyzed by non-enantioselective ultra-high performance micro-flow liquid chromatography (Waters ACQUITY UPLC® M-Class HSS T3 column, 0.1% formic acid and acetonitrile with 0.1% formic acid, 14 µL/min flow rate) coupled with tandem mass spectrometry in positive scheduled multiple reaction monitoring mode. Validation parameters such as linearity, precision, recovery, accuracy, stability, limit of detection (LOD), and limit of quantification (LOQ) were proven. LOD for KET and NK was 0.08 ng/mL and LOQ were 0.5 ng/mL and 0.6 ng/mL, respectively. For HNK, LOD was 0.1 ng/mL and LOQ 0.8 ng/mL. The method was then successfully applied to quantify KET, HNK, and NK in blood serum samples from subjects who received KET intravenously. A novel method for the simultaneous analysis of KET, NK, and HNK was established. This new method could now be used for clinical trials investigating KET and its metabolites HNK and NK or for forensic analysis in order to confirm KET abuse.
CRIS-Team Scopus Importer:2020-06-16
Keywords: cis-6-Hydroxynorketamine; Human blood serum; Ketamine; MicroLC–ESI–sMRM; Norketamine; Targeted mass spectrometry